Topological Indices Polynomials of Domination David Derived Networks - Anjaneyulu Mekala; Vijaya Chandra Kumar U; R. Murali (مجلة بغداد للعلوم)
The chemical properties of chemical compounds and their molecular structures are intimately connected. Topological indices are numerical values associated with chemical molecular graphs that help in understanding the physicochemical properties, chemical reactivity and biological activity of a chemical compound. This study obtains some topological properties of second and third dominating David derived (DDD) networks and computes several K Banhatti polynomial of second and third type of DDD.